Exploring the Relationship between Metacognitive Strategies and Reading Comprehension among Senior High School Students - Dewi, Desi Surlitasari; Premini, Deviany (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
This study was intended to find out whether there is any significant correlation between students’ metacognitive strategies and students’ reading comprehension. Besides, it aimed to find out whether the variables had a positive or negative correlation. Therefore, the researcher conducted a correlational research. The population of the study was 286 and the sample was 37 students of tenth grade of SMA N 19 Batam taken by cluster random sampling. Questionnaires of Survey of Reading Strategies (SORS) were used as instruments to measure the students’ metacognitive strategies and Reading Comprehension test was used to assess students’ reading comprehension. Then, the researcher found out the validity and reliability of both instruments. After finding out that the distribution of the data was normal, the researcher analyzed the correlation by using Person Product Moment formula to find out the correlation both students’ metacognitive (X variable) and students’ reading comprehension (Y variable).The data analysis found that rcount was – (0.056) means that the variables had a negative correlation. Then, it showed that (0,331) and . It indicates that was smaller than . It means that alternative hypothesis is rejected and null hypothesis is accepted. The research found out that there was no significant correlation between students’ metacognitive and students’ reading comprehension at tenth grade of SMA N 19 Batam.